AN ERRORS ANALYSIS OF LANGUAGE USING BY THE STUDENTS' IN SPEAKING ACTIVITIES AT MA'HAD OF STATE ISLAMIC INSTITUTE OF KERINCI - Oki Mitra; Ainil Khuryati; Ilal Musallin; Widad Binti Mat Zin (UNiversitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This thesis examines the analysis of students' competence in understanding conversation on the program